2007
DOI: 10.1111/j.1440-169x.2007.00965.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of a transcription factor Pax6 in the developing vertebrate olfactory system

Abstract: The olfactory system is responsible for capturing and processing odorant information, which significantly influences a variety of behaviors in animals. The vertebrate olfactory system consists of several neuronal components including the olfactory epithelium, olfactory bulb and olfactory cortex, which originate from distinct embryonic tissues. The transcription factor Pax6 is strongly expressed in the embryonic and postnatal olfactory systems, and regulates neuronal specification, migration and differentiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 75 publications
0
32
0
Order By: Relevance
“…lens, retina, cornea, iris, olfactory epithelium, forebrain, cerebellum, and pancreas) (41,43,44,79). It has been shown that Pax6 regulates the batteries of common target genes in distinct tissues, including the lens and neurons (57,80).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…lens, retina, cornea, iris, olfactory epithelium, forebrain, cerebellum, and pancreas) (41,43,44,79). It has been shown that Pax6 regulates the batteries of common target genes in distinct tissues, including the lens and neurons (57,80).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in contrast to the majority of sequencespecific DNA binding proteins that use a single DNA-binding domain that typically docks with 6 -10 bp of DNA, Pax6 can use ␤-sheets, PAI, linker, RED, and HD, and their various combinations to bind DNA. Although some important direct targets of Pax6 genes have been identified (41), a large body of work remains to be accomplished (42)(43)(44). Some transcription factors, especially those with multiple DNA-binding subdomains (e.g.…”
mentioning
confidence: 99%
“…The transcription factor Pax6 is highly conserved among vertebrates and is essential for a wide variety of developmental processes within the central nervous system (CNS), sensory organs, and the endocrine system [15][16][17][18][19]. Homozygous Pax6 mutant mice (Pax6…”
Section: Introductionmentioning
confidence: 99%
“…for the development of various tissues and organs, particularly the eye and the nervous system (18,20,(27)(28)(29)(30)(31). Here we reported a new splicing isoform of Pax6, Pax6(S), whose C terminus (PST N S) is composed of a truncated canonical PST domain and a unique S tail.…”
Section: Pax6(s) Is a Novel Splicing Isoform Of Pax6-pax6 Is Criticalmentioning
confidence: 99%